The effect of different industrialized building system (IBS) construction methods compared to the conventional method on occupational safety and health (OSH) industry risks in construction - Mohd Amin, Mohamad Ariff (2021)
The construction industry is known for the hazardous physical working conditions and high risk of accidents because of the nature of the workplace activities. It is one of the most dangerous business sectors compared to the other industries. The accident cases in construction industry contribute to the rises statistics of accidents in Malaysia. Therefore, IBS construction has been suggested to replace the many initiatives that could be implemented to improve OSH performance due to frequent accidents as a substitute for the traditional construction methods. Improving the performance of the construction industry has pushed forward the need for innovation and adopting new construction methods and technologies in the industry. This study aims to analyze and validate the impact of major activities of the IBS construction method which are prefabricated steel framing system, prefabricated timber framing system and formwork system. This study involved a field observation to on-site that use these 3 types of IBS as a residential building construction method. The data was collected through interviews with the safety and health officers, other than observed the operations involved in each type of IBS method to determine the major activities and OSH risks associated throughout the construction process of the IBS. Next, the activities and the risks involved in each activity were tabulated before it was analyzed and validated with the competent professionals. The findings revealed that the major activities in the prefabricated timber framing system and formwork system have low risk compared to the conventional method. Meanwhile, majority of the activities involved in the prefabricated steel framing system has high risk compared to the conventional method. Moreover, 2 methods have introduced new activities which are prefabricated steel framing system (2 new activities) and prefabricated timber framing system (4 new activities). Therefore, this study offered a better understanding of the risk/hazard of IBS construction method and the effect the IBS towards safety and health.